Comparative treatment costs of risk‐stratified therapy for childhood acute lymphoblastic leukemia in India. (15th August 2022) - Mungle, Tushar; Das, Nandana; Pal, Saikat; Gogoi, Manash Pratim; Das, Parag; Ghara, Niharendu; Ghosh, Debjani; Arora, Ramandeep Singh; Bhakta, Nickhill; Saha, Vaskar; Krishnan, Shekhar
Abstract: Background: To evaluate the treatment cost and cost effectiveness of a risk‐stratified therapy to treat pediatric acute lymphoblastic leukemia (ALL) in India. Methods: The cost of total treatment duration was calculated for a retrospective cohort of ALL children treated at a tertiary care facility. Children were risk stratified into standard (SR), intermediate (IR) and high (HR) for B‐cell precursor ALL, and T‐ALL. Cost of therapy was obtained from the hospital electronic billing systems and details of outpatient (OP) and inpatient (IP) from electronic medical records. Cost effectiveness was calculated in disability‐adjusted life years. Results: One hundred and forty five patients, SR (50), IR (36), HR (39), and T‐ALL (20) were analyzed. Median cost of the entire treatment for SR, IR, HR, and T‐ALL was found to be $3900, $5500, $7400, and $8700, respectively, with chemotherapy contributing to 25%–35% of total cost. Out‐patient costs were significantly lower for SR ( p  < 0.0001). OP costs were higher than in‐patient costs for SR and IR, while in‐patient costs were higher in T‐ALL. Costs for non‐therapy admissions were significantly higher in HR and T‐ALL ( p  < 0.0001), representing over 50% of costs of in‐patient therapy. HR and T‐ALL also had longer durations of non‐therapy admissions. Based on WHO‐CHOICE guidelines, the risk‐stratified approach was very cost effective for all categories of patients. Conclusions: Risk‐stratified approach to treat childhood ALL is very cost‐effective for all categories in our setting. The cost for SR and IR patients is significantly reduced through decreased IP admissions for both, chemotherapy and non‐chemotherapy reasons. Abstract : With the ICiCLe‐ALL‐14 risk stratified approach, ALL treatment cost for low‐risk patients is significantly lower as compared to intermediate and high‐risk groups. Additionally, it is a cost‐effective intervention in a low‐middle income country.